Transcriptional response to prolonged acid exposure and genetic divergence in Helicobacter pylor - Dong, Quanjiang (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2003)
Helicobacter pylori infection is strongly associated with gastritis, peptic ulcer and gastric adenocarcinoma. Molecular mechanisms involved in H. pylori adaptation and clinical consequences of infection are unclear. This study aimed to investigate transcriptional response to acid exposure and inter-strain genetic diversity.
Keywords: Clinical Medicine, Ph.D.; Ph.D. Trinity College Dublin